Monotheisme Yahudi Kuno dan Doktrin Trinitas - Deky Hidnas Yan Nggadas (JURNAL LUXNOS, 2018)
Abstract: This study examines ancient Jewish monotheism and compares it with the doctrine of the trinity in the Bible, particularly in Paul's epistles (Ephesians) and the Gospel of John. Researchers used qualitative methods with an emphasis on biblical studies. Researchers conclude that triadic patterns are central to Paul's theology in Ephesians. On the other hand, from the point of view of the practice of worship and devotion, early Christianity seemed to be dominated by a binitarian or diadid pattern of worship (as Hurtado argues). Was the Holy Spirit worshiped in the worship practices and devotion of early Christianity? The evidence from the NT forces us to refrain from giving positive answers to this question. This does not mean that the Holy Spirit is not presented as God (cf. John 14-16; etc.), but that the objects of recipients of worship and devotion in the NT pages are dominated by the Father and the Son. This pattern of worship finds its background not in the Greco-Roman religions, but in ancient Jewish monotheism. From ancient Jewish monotheism too, we find reference to the Christology of divine identity which was so dominant in the NT. Abstrak: Penelitian ini mengkaji tentang monoteisme Yahudi kuno dan membandingkannya dengan doktrin trinitas dalam Alkitab, khususnya dalam surat Paulus (Surat Efesus) dan juga Injil Yohanes. Peneliti menggunakan metode kualitatif dengan menitikberatkan pada kajian biblika. Peneliti menyimpulkan pola-pola triadik merupakan pusat teologi Paulus dalam Surat Efesus. Di sisi lain, dari segi praktik penyembahan dan devosinya, Kekristenan mula-mula tampaknya didominasi oleh pola penyembahan yang binitarian atau diadik (seperti argumentasi Hurtado). Apakah Roh Kudus disembah dalam praktik penyembahan dan devosi Kekristenan mula-mula? Bukti-bukti dari PB memaksa kita untuk menahan diri dalam memberikan jawaban positif terhadap pertanyaan ini. Hal ini tidak berarti bahwa Roh Kudus tidak dipresentasikan sebagai Allah (bnd. Yoh. 14-16; dll.), namun memang objek penerima penyembahan dan devosi dalam halaman-halaman PB didominasi oleh Bapa dan Anak. Pola penyembahan ini, mendapatkan latar belakangnya bukan dalam agama-agama Greco-Roman, melainkan dalam monotheisme Yahudi kuno. Dari monotheisme Yahudi kuno juga, kita mendapati acuan bagi Kristologi identitas ilahi yang sangat dominan dalam PB.